1982
DOI: 10.1042/bj2020363
|View full text |Cite
|
Sign up to set email alerts
|

Muscle protein synthesis in the streptozotocin-diabetic rat. A possible role for corticosterone in the insensitivity to insulin infusion in vivo

Abstract: The effect of insulin infusion in vivo on muscle protein synthesis was investigated in rats. In 10-days-streptozotocin-diabetic rats infused in vivo with amino acids and glucose, the rate of protein synthesis per unit of RNA (RNA activity) was markedly decreased. Pre-treatment with large doses of insulin at 17 and 1 h before the infusion fully restored RNA activity to normal. Infusion of insulin for 6 h with amino acids and glucose did not restore RNA activity to normal in the diabetic rats. However, in diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2

Year Published

1983
1983
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 21 publications
(32 reference statements)
4
33
2
Order By: Relevance
“…Interestingly, muscles from insulin-deficient diabetic animals, which exhibit depressed rates of protein synthesis in vitro, do respond to insulin during the initial period of perfusion (4,7). In keeping with these observations, in vivo studies have readily shown an impairment in muscle protein synthesis in diabetic animals, which is at least partially reversible with insulin (27)(28)(29)(30), while stimulation of synthesis by insulin in nondiabetic animals has proved far more difficult to demonstrate (28). These considerations, coupled with the present study results, raise the possibility that the stimulatory effect of insulin on protein synthesis may be manifest in vivo at normal postabsorptive insulin concentrations.…”
Section: Introductionmentioning
confidence: 52%
“…Interestingly, muscles from insulin-deficient diabetic animals, which exhibit depressed rates of protein synthesis in vitro, do respond to insulin during the initial period of perfusion (4,7). In keeping with these observations, in vivo studies have readily shown an impairment in muscle protein synthesis in diabetic animals, which is at least partially reversible with insulin (27)(28)(29)(30), while stimulation of synthesis by insulin in nondiabetic animals has proved far more difficult to demonstrate (28). These considerations, coupled with the present study results, raise the possibility that the stimulatory effect of insulin on protein synthesis may be manifest in vivo at normal postabsorptive insulin concentrations.…”
Section: Introductionmentioning
confidence: 52%
“…There is evidence that this elevated corticosterone concentration inhibits the effects of exogenously applied insulin on muscle protein synthesis (Odedra & Millward, 1982;Odedra et al 1982). This is another example of a possible interrelationship between hormones, although in this case it would be more interesting if the relationship could be demonstrated in 'normal' animals.…”
Section: Symposium Proceedings I983mentioning
confidence: 99%
“…Presumably this insulin is 'attempting' to counteract the catabolic effects of the glucocorticoids (Odedra & Millward, 1982). In diabetic rats, administration of insulin does not stimulate protein synthesis in muscle unless the animal is adrenalectomized; diabetic rats have higher corticosterone concentrations than controls (Odedra et al 1982). It is also interesting to note that while insulin promotes the uptake of amino acids into muscle, cortisol promotes an increased efflux of amino acids from muscle (Rannels & Jefferson, 1980;Lewis & Goldspink, 1982).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The glucocorticoidinduced hyperinsulinemia could not overcome this insulin resistance [60]. The [85].…”
mentioning
confidence: 99%